(untitled) (Eurasian Research Bulletin, 2023)
Aim of the investigation - to learn protein providing condition of the professional sportsmen, who experience of the fight kurash in the background regulation nutrition. Have been studied findings of the professional sportsmen, who experience of the fight kurash in the background regulation. Examined men between 18-30, who are in regulation nutrition. Estimated increasing of the quota of creatinin in the general amount of the nitrogen, which testifies strengthen of the protein catabolism in the organism of the professional sportsmen. Have been determined redivision of the form of the nitrogen extracting with urine, expressing in the view of decreasing amount of the urine and increasing of the creatinin in the common amount urine, that allows to conclude about inadequate provision of the organism of the sportsmen with nutritional protein. Calculated creatin index (9.1) shows to weaken degree of the protein energetic insufficiency in fighters.